2010
DOI: 10.1093/ije/dyp389
|View full text |Cite
|
Sign up to set email alerts
|

An adequacy evaluation of a 10-year, four-country nutrition and health programme

Abstract: Background Evaluations of large-scale health and nutrition programmes in developing countries are needed for determining the effectiveness of interventions. This article critically analyses a non-governmental organization (NGO)-led large-scale, multi-country, 10-year micronutrient and health (MICAH) programme with an ‘adequacy evaluation’, that is, a documentation of time trends in the expected direction.Methods MICAH was implemented from 1996 to 2005 in selected areas of Ethiopia, Ghana, Malawi and Tanzania, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
1
28
0
1
Order By: Relevance
“…SDs of HAZ per site indicated data quality similar to other studies that reported on HAZs of children ,2 y of age (9,28,33). Stunting prevalence at baseline ranged from 25% to 77%.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…SDs of HAZ per site indicated data quality similar to other studies that reported on HAZs of children ,2 y of age (9,28,33). Stunting prevalence at baseline ranged from 25% to 77%.…”
Section: Resultssupporting
confidence: 77%
“…Predictive models suggested that by combining food and micronutrient supplementation, fortification, and disease-control interventions, stunting prevalence could be reduced by one-third (7). Although a number of global health initiatives have attempted to deliver such multicomponent interventions in sub-Saharan Africa, large-scale evaluations have shown limited effects on stunting even with high levels of coverage (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have found that maternal recall of breastfeeding is reliable [67,68], even 20 years after the time of breastfeeding [69]. Another limitation is our inability to thoroughly evaluate the possible role of Reverse Causation.…”
Section: Limitationsmentioning
confidence: 98%
“…Cases in Nicaragua (Mora, ), Nepal (Pokharel et al, ), Northwest Vietnam (Casey et al, ; Passerini et al, ) and Ghana (MacDonald et al, ) outlined the role of local and international NGOs as both active forces in filling public‐health system at macro and microlevels, capacity building of human resource, and implementing health activities. They covered a broad range of tasks from providing regular, intensive technical support and training, funds, staff and expert consultants to conducting monitoring and adequacy evaluations or undertaking large‐scale health interventions as observed in the MICAH programme (Berti, Mildon, Siekmans, Main, & Macdonald, ). Most importantly, the selected cases evidenced that during the implementation period, anaemia and potentially related complications such as maternal or infant mortality and low birth‐weight, showed a significant decrease that occurred concurrently to the increase of women of reproductive age taking IFA and attending ante‐natal care.…”
Section: Discussionmentioning
confidence: 99%